2013
DOI: 10.1001/jamaneurol.2013.3521
|View full text |Cite
|
Sign up to set email alerts
|

Orthostatic Tremor, Progressive External Ophthalmoplegia, and Twinkle

Abstract: Mutant Twinkle increases dopaminergic neurodegeneration, mtDNA deletions and modulates Parkin expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
0
9
1
Order By: Relevance
“…However, our findings corroborate and further extend three previous smaller reports10 19 20 that also failed to find reductions in striatal dopamine transporter tracer binding and indeed dopaminergic drugs are unhelpful for OT. Finally, despite rare reports of cerebellar ataxia associated with OT,7 8 21 22 we could not identify any in our cases. Although patients with OT might increase stance width, this could be compensatory to overcome the feeling of unsteadiness and/or fear of falling when standing 16…”
Section: Discussioncontrasting
confidence: 66%
“…However, our findings corroborate and further extend three previous smaller reports10 19 20 that also failed to find reductions in striatal dopamine transporter tracer binding and indeed dopaminergic drugs are unhelpful for OT. Finally, despite rare reports of cerebellar ataxia associated with OT,7 8 21 22 we could not identify any in our cases. Although patients with OT might increase stance width, this could be compensatory to overcome the feeling of unsteadiness and/or fear of falling when standing 16…”
Section: Discussioncontrasting
confidence: 66%
“…Mutations in C10orf12, as well as the mitochondrial replicase, POLG, are associated with mitochondrial DNA depletion and/or deletions with muscle biopsy findings typically involving multiple respiratory chain complex enzyme deficiency and immunohistochemical evidence of cytochrome oxidase (complex IV)-deficient muscle fibers (36). In individuals with myopathy related to MELAS, skeletal muscle biopsy may demonstrate the presence of ragged red fibers, indicative of mitochondrial proliferation (37). Seminal studies are additionally reviewed in (38).…”
Section: Discussionmentioning
confidence: 99%
“…There is a single study that has identified a C10orf2 Twinkle mutation in a man with OT in his late sixties and progressive external ophthalmoplegia. 19 Twinkle is a nuclear-encoded human mitochondrial DNA helicase. 19 This observation raises the question of a possible role of mitochondrial dysfunction in the genesis of OT.…”
Section: Risk and Etiological Factorsmentioning
confidence: 99%